2022
DOI: 10.1108/md-06-2021-0788
|View full text |Cite
|
Sign up to set email alerts
|

Mapping talent agility: a bibliometric analysis and future research agenda

Abstract: PurposeThis study explores the concept of “talent agility” since its inception using bibliometric analysis and paves the way for future research agenda in the field of business and management.Design/methodology/approachThe articles were retrieved from the Scopus database comprising 67 publications from 2001 to September 2020. This study has applied bibliometric techniques such as citation analysis, co-citation analysis, bibliographic coupling, co-authorship analysis, and co-occurrence keyword analysis.Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…This multidimensional framework constitutes a seminal contribution to human resource management by engendering a more comprehensive and holistic comprehension of compensation and its interplay with other organizational factors, such as employee performance, job characteristics and organizational strategy. Firstly, the proposed model substantiates the resource-based view of the firm by recognizing human capital as an invaluable resource that could enable organizations to gain and maintain a competitive edge (Gouda and Tiwari, 2022;Sultana et al, 2022;Sotula and Anning, 2022;Shahzad et al, 2022;Shams and Solima, 2019;Bayon et al, 2016). Accurate compensation predictions facilitate organizations to attract, retain and nurture highly proficient employees with exceptional knowledge and skills, thereby fostering the organization's competitive advantage.…”
Section: Theoretical Implicationsmentioning
confidence: 75%
See 2 more Smart Citations
“…This multidimensional framework constitutes a seminal contribution to human resource management by engendering a more comprehensive and holistic comprehension of compensation and its interplay with other organizational factors, such as employee performance, job characteristics and organizational strategy. Firstly, the proposed model substantiates the resource-based view of the firm by recognizing human capital as an invaluable resource that could enable organizations to gain and maintain a competitive edge (Gouda and Tiwari, 2022;Sultana et al, 2022;Sotula and Anning, 2022;Shahzad et al, 2022;Shams and Solima, 2019;Bayon et al, 2016). Accurate compensation predictions facilitate organizations to attract, retain and nurture highly proficient employees with exceptional knowledge and skills, thereby fostering the organization's competitive advantage.…”
Section: Theoretical Implicationsmentioning
confidence: 75%
“…As these technological adaptations burgeon, an agile and highly skilled workforce is imperative. They are the actual recipients of these innovative technological advancements and are responsible for engendering the foundational products underpinning them (Gouda and Tiwari, 2022;Ponta et al, 2021). Moreover, the contentment of such a workforce eventuates in increased productivity, engagement and substantial impact on corporate performance and organizational culture at large (Chatterjee et al, 2022;Bendickson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been observed that international cooperation between different authors and countries is quite successful in other areas of business and management. For instance, the USA has the highest collaboration network with European countries like the UK, France, Spain, Germany and Italy in the area of strategic management (Kosch and Szarucki, 2020; Gouda and Tiwari, 2022). Further, it has been observed that collaboration among developed countries is well established in comparison to collaboration among developing countries.…”
Section: Resultsmentioning
confidence: 99%
“…Performance analysis includes performance metrics such as total publication (TP) and citation metrics such as number of cited publications (NCPs), total citations (TCs), average citation per paper (C/P), average citation per cited paper (C/CP), h-index, and g-index [62,63]. Science mapping examines the relationships that exist in each research component such as co-citation, co-occurrence, and co-authorship [64]. Science mapping visualizes the scientific links and systematic patterns within the research area to find connected research themes [65][66][67].…”
Section: Introductionmentioning
confidence: 99%